The Palgrave Handbook of Paralympic Studies (Palgrave Macmillan UK, 2018)
This handbook provides a critical assessment of contemporary issues that define the contours of the Paralympic Movement generally and the Paralympic Games more specifically. It addresses conceptualisations of disability sport, explores the structure of the Paralympic Movement and considers key political strategic and governance issues which have shaped its development. The Palgrave Handbook of Paralympic Studies is written by a range of international authors, a number of whom are senior strategists as well as academics, and explores legacy themes through case studies of recent Paralympic games. Written in the wake of the 2016 Rio Paralympic Games, it provides an assessment of contemporary challenges faced by the International Paralympic Committee and other key stakeholders in the Paralympic Movement. Its critical assessment of approaches to branding, classification, social inclusion and technological advances makes this handbook a valuable resource for undergraduate study across a range of sport and disability related programmes, as well as a point of reference for researchers and policy makers.